5,13-Disulfamoyl-1,9-diazatetracyclo[7.7.1.0(2,7).0(10,15)]heptadeca-2(7),3,5,10,12,14-hexaen-1-ium chloride - Xu, Yichao (International Union of Crystallography, 2011)
In the title salt, C(15)H(17)N(4)O(4)S(2) (+)·Cl(−), the chloride anion is disordered over two positions with occupancies of 0.776 (6) and 0.224 (6). The cation adopts an L shape and the dihedral angle between the benzene rings is 82.5 (3)°. In the crystal, inversion dimers of cations linked by pairs of N—H⋯N hydrogen bonds occur, with the bond arising from the protonated N atom. The cationic dimers are linked into chains via the disordered chloride ions by way of N—H⋯Cl hydrogen bonds and N—H⋯O, C—H⋯O and C—H⋯Cl interactions also occur, which help to consolidate the three-dimensional network.